Pengembangan Ulang Sistem Informasi Akademik SMK demi Pemanfaatan dan Peningkatan yang Berkelanjutan - Iqbal Santosa; Edi Sutoyo; Rahmat Fauzi (Universitas Muhammadiyah Surakarta, 2023)
Daarut Tauhid Boarding School Vocational School (SMKDTBS) Bandung has implemented SIAKAD Online since 2019, but the school feels that the implementation is still not optimal and needs to be redeveloped because this system has not been able to meet the needs of stakeholders and since 2021 it has no longer received financial support for development. This is a gap that must be completed by the school, considering that the development of information technology, especially in the academic field, has increased significantly, especially with the increasing trend of working from home since the pandemic. An academic information system is needed that suits the needs of stakeholders and can ensure the continuity, sustainability, and even increased achievement of SMKDTBS Bandung. The Community Service Program (PkM) will answer this need, with the development of the first phase of SIAKAD which will be carried out within a period of 4 months from March to May 2022 by the PkM team consisting of 3 lecturers and 2 students. PkM is carried out in several stages: the needs gathering stage produces ERD, use case diagrams, activity diagrams, and SIAKAD mockups; the development stage produces a system with features that have been adapted to current needs; the stage of preparing the guidebook to produce a guidebook for using SIAKAD; the training stage is carried out by training on SIAKAD installation and its development environment for teachers who act as admins; finally, the evaluation phase obtained positive feedback from the school who felt helped by the re-development of SIAKAD. After PkM is completed, it is hoped that the development of SIAKAD can continue, at a more affordable cost because it can be carried out independently by admin teachers at SMKDTBS, so that in the end all school management processes are integrated into just one system.